Impact of Number of Foreign and Domestic tourists on Occupancy Rates, ADR, and RevPar - Dr. M.S Annapoorna, Binny Cherian (Drugs and Cell Therapies in Hematology, 2021)
Sustainability of the hospitality industry depend on the occupancy rates, ADR, revenue per and the number of tourist travelling to other destinations and staying in the hotels. At this time of the year when uncertainties prevail due to the coronavirus, restrictions imposed on travelling, cancellation of the business trips, cancellations of the family trips, led to reduction in the occupancy rates, ADR and Revenue per room and many questions raised on the sustainability of the hotel industry. It is the right time to contemplate upon the factors affecting the occupancy rates, ADR, Revpar and the impact of these factors on the sustainability and growth of the hotel industry. The study chooses the Indian Hotel industry during the period of 2001-2019 as its application setting.